PERBANDINGAN BREAST CARE DAN PIJAT OKSITOSIN TERHADAP PRODUKSI ASI PADA IBU POST PARTUM NORMAL - Agianto; Latifah, Juhar; Wahid, Abdurahman (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2015)
Breast milk is the best food for babies, because it contains all the nutrients the ideal amount andcomposition required by infants. One of the obstacles in the early breastfeeding is the production ofbreast milk in small quantities on the first day after birth. Ways that can be done to increase milkproduction is the treatment of breast care and massage oxytocin. This study aimed to compare thebreast care with massage oxytocin on milk production in mothers of normal post partum. Thisresearch quantitative with quasy experimental study design, 32respondents with consecutivesampling, used independent t-test. Milk production in mothers with a normal post partum breast careaction has an average number of 31.4375, while the production of milk with a massage action ofoxytocin has an average number of 24.8750. Test independent sample t test showed that the results ofthe t> t table (2.858> -2.037) and the value of p <0.05 (0.008 <0.05). Based on research carried outcan be concluded that there is a difference between the breast care with massage oxytocin on milkproduction in mothers of normal post partum.